Molecular identification of clinical isolates of Fusarium in Colombia (2018)
ABSTRACT: Objective Identifying Fusarium isolates from mycosis symptomatic patients through molecular techniques as PCR and sequencing. Methods In this study, samples were taken from 101 mycosis symptomatic patients in-between 2004-2006. To determine isolates belonging to the Fusarium genus, the DNAr 28S region was amplified through PCR and specific PCR primers further confir-med their identity to the species level. Additionally, in order to confirm the identity of the species of the isolates, 75 isolates of these were analyzed by partial sequencing of the 28S rDNA and the TEF1-α gene. Results The 28S rDNA portion detected all 101 isolates as belonging to Fusarium and the PCR specific primers detected 52 and 29 isolates as F. oxysporum and F. solani, respectively; 34 and 41 of these, afterwards studied by partial sequencing of the 28S rDNA and TEF1-α genes respectively, were effectively identified by the technique. Conclusion From all the molecular markers used to identify Fusarium isolates, the sequence of the TEF1-α gene provided the best resolution in the identification of species level; however it is possible to discriminate between F. oxysporum and F. solani isolates by PCR, in most of the cases, what is important considering the simplicity of the technique and a faster diagnosis.